Förderpreis Junge Künstler 1990. - Fiedler-Bender, Gisela; Munkes, H.J.; Schmitt, Werner (Saarbrücken : Saar Ferngas Aktiengesellschaft, 1990)
Wille, Barbara ; Boecker, Arvid ; Schewior, Sigrid ; Bahr, Thomas ; Beck, Silvia ; Berrar, Francis ; Burlafinger, Sylvia ; Deffert, Liane ; Eicher, Margret ; Enders, Erika ; Freyer, Lutz ; Holzkamp, Philipp ; Hundhausen, Martin ; Klomann, Dirk ; Kreiensiek, Joachim ; Kreissler, Marion ; Lennert, Volker ; Löcherbach, Roger ; Martin, Franz ; März, Volker ; Nikolai, Andreas ; Oswald, Karlheinz ; Piwowarsky, Jutta ; Poppe, Dagmar ; Rech, Werner ; Schick, Martin ; Schmenger, Thomas ; Schmidt, Markus ; Schubert, Sabine ; Uhl, Christian ; Wagner, Gabi ; Wendels, Franziskus
biografie
Förderpreis Junge Künstler 1990, Saar Ferngas Aktiengesellschaft, Saarbrücken, 1990
Duits
boek